2005
DOI: 10.1021/cc0500607
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Identification of Linear B-Cell Epitopes and Entry-Blocking Peptide of Severe Acute Respiratory Syndrome (SARS)-Associated Coronavirus Using Synthetic Overlapping Peptide Library

Abstract: A 10-mer overlapping peptide library has been synthesized for screening and identification of linear B-cell epitopes of severe acute respiratory syndrome associated coronavirus (SARS-CoV), which spanned the major structural proteins of SARS-CoV. One hundred and eleven candidate peptides were positive according to the result of PEPscan, which were assembled into 22 longer peptides. Five of these peptides showed high cross-immunoreactivities (approximately 66.7 to 90.5%) to SARS convalescent patients' sera from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 43 publications
3
61
1
1
Order By: Relevance
“…It has been reported that SARS CoV S DNA vaccine could induce neutralizing antibodies, which played important roles in protective immune responses to virus infection. Furthermore, several B cell epitopes, such as S471-503, S803-828, S1061-1093, S335-352 and S442-458, in SARS CoV S protein were identified [39][40][41]. However, T cell epitopes N50 and N60 could not generate antibodies in our study, indicating that N50 and N60 could not be B cell epitopes.…”
Section: Discussioncontrasting
confidence: 60%
“…It has been reported that SARS CoV S DNA vaccine could induce neutralizing antibodies, which played important roles in protective immune responses to virus infection. Furthermore, several B cell epitopes, such as S471-503, S803-828, S1061-1093, S335-352 and S442-458, in SARS CoV S protein were identified [39][40][41]. However, T cell epitopes N50 and N60 could not generate antibodies in our study, indicating that N50 and N60 could not be B cell epitopes.…”
Section: Discussioncontrasting
confidence: 60%
“…They demonstrated that five of assembled 22 longer peptides showed high crossimmunoreactivities to 42 SARS convalescent patients' sera from the severest epidemic regions of the China mainland. Among them, S471-503, a peptide located at the receptor binding domain (RBD) of SARS-CoV, could specifically block the binding between the RBD and angiotensin-converting enzyme 2, resulting in the inhibition of SARS-CoV entrance into host cells in vitro [35]. In current study, we demonstrated a linear B-cell antigenic epitope located in the M protein between 1 and 15 aa, which was consistent with the previous reports [7,8].…”
Section: Discussionsupporting
confidence: 91%
“…Lane 1: total cellular extracts from IPTGinduced BL21 transformed with recombinant pSARS-M construct (control); Lane 2: total cellular extracts from IPTGinduced BL21 transformed with recombinant pSARS-Ml construct; Lane 3: total cellular extracts from IPTG-induced BL21 transformed with recombinant pSARS-M2 construct antigenic epitope(s) may still locate in this region. While Hu et al has identified the B-cell antigenic epitope on S2 protein, they also found that two synthesized overlapping peptides, both of which were located within amino acids 29-48 of M protein, could react to mixture of 42 SARS convalescent patients' sera, indicating that other potential B-cell antigenic epitope(s) may still locate in this region [35]. Meanwhile, our experiment showed that the recognizing region of the MAb against M fragment was in the M protein between amino acids 16 and 28.…”
Section: Discussionmentioning
confidence: 99%
“…[8,13,14] Similar ideas could be applied in de-veloping2 019-nCoV vaccines. [22] Onep eptide comprising two ACE2 motifs (aa 22-44a nd 351-357) linked by glycine exhibited potent anti-SARS activity with an IC 50 value of 0.1 mm. [15] Although there are published resultsa bout therapeutic antibodiesa nd peptides developed to neutralize the SARS-CoV spike protein, they are expectedt oh ave little use in neutralizing 2019-nCoV.A sd iscussed above, the two engaging regions in the spike RBD for bindingA CE2 are very different between SARS-CoV and 2019-nCoV.A ntibodies and peptides targeting two regions in the SARS-CoV RBD are expected to interact weaklyw itht he 2019-nCoV RBD.…”
Section: The Spike Proteinmentioning
confidence: 99%